Pengaruh Pelaksanaan Discharge Planning Terstruktur Terhadap Kepuasan Pasien di Rumah Sakit Natar Medika - Neliwati; Elasari, Yunina; Wulandari, Rizki Yeni; Kurniawan, Moh Heri (Journal of Nursing Invention, 2024)
Background: Discharge Planning is a continuous process that must be started or implemented since the patient is admitted and hospitalized in the hospital with the aim of helping patients and families in improving or maintaining their health. Discharge planning for patients who are being treated has not been implemented optimally because the role of nurses is still limited to carrying out routine activities only, namely only in the form of information about the re-check schedule Objective: The purpose of this study is to optimize the implementation of Discharge planning at Natar Medika Hospital. Method: The research design used was quantitative research with a pre-experimental approach conducted on August 1-25, 2024. The sample in this study was 40 patients in the inpatient room of Natar Medika Hospital, with a purposive sampling technique. The statistical test in this study used the Wilcoxone test. Results: The results of the univariate analysis obtained results from 40 respondents before being given socialization of the implementation of discharge planning, the most was less than 30 people (75%), after being given socialization, the most was good with 35 people (85.5%), the results of the bivariate analysis showed a p-value of 0.000 <0.05 there was an effect of socialization on the implementation of structured discharge planning at Natar Medika Hospital in 2024, and the implementation of structured discharge planning at Natar Medika Hospital has been running optimally. Conclusion: The suggestion from this study for the management of Natar Medika Hospital is to carry out a supervision process related to the implementation of discharge planning for nurses so that structured discharge planning activities when patients are treated at the hospital until the patient is declared home can run optimally.